THE EFFECT OF GINGER DRINKING ON BREAST MILK PRODUCTION TO WOMEN IN THE PUBLIC PERIOD IN NGEMBAK VILLAGE - Maylia Arviyanti; Sehmawati; Dewi Sapta Wati (LPPM AN NUUR, 2024)
Background ; One of the causes of the pattern of infant mortality in Indonesia is that less than half of children aged 12-17 months do not receive breast milk. According to WHO in 2020, exclusive breastfeeding coverage is around 44%, while coverage in Indonesia is only 42% of babies receiving exclusive breastfeeding. One of the reasons why mothers stop breastfeeding their babies is lactation insufficiency (low breast milk supply). Treatment given to increase breast milk production is giving ginger drink which contains galactogue which can increase breast milk production.Objective ; To analyze the effect of giving ginger drink on breast milk production in postpartum mothers.Methodology ; This research is a quantitative research using a quasi-experimental design with a one group pretest posttest design. The sampling technique was purposive sampling with a sample of 22 respondents.Results ; Based on SPSS using the paired sample t-Test with a p-value of 0.000. If α <0.05 then Ho is rejected and Ha is accepted, which means that there is an influence of giving ginger drink on breast milk production in postpartum mothers in Ngembak Village.Conclusion ; Based on this research, there is an effect of giving ginger drink on breast milk production in postpartum mothers in Ngembak Village